2014
DOI: 10.1002/2014gl061584
|View full text |Cite
|
Sign up to set email alerts
|

Slow translation speed causes rapid collapse of northeast Pacific Hurricane Kenneth over cold core eddy

Abstract: Category 4 Hurricane Kenneth (HK) experienced unpredicted rapid weakening when it stalled over a cold core eddy (CCE) on 19-20 September 2005, 2800 km SE of Hawaii. Maximum sea surface temperature (SST) cooling of 8-9°C and a minimum aerially averaged SST of 18.3°C (over 8750 km 2 ) characterized its cool wake. A 3-D mixed-layer model enabled estimation of enthalpy fluxes (latent and sensible heat), as well as the relative importance of slow translation speed (U h ) compared with the preexisting CCE. As U h dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 33 publications
(64 reference statements)
1
59
0
Order By: Relevance
“…The observational and numerical studies have shown that rapid intensification can occur when the storm passes over a warm ocean eddy. In contrast, when the TC encounters a cold ocean eddy, the SST cooling can be enhanced, and thus TC intensity would be further limited due to the stronger negative feedback associated with the decrease of the heat flux from the ocean [ Lin et al ., , ; Wu et al ., ; Sung et al ., ; Walker et al ., ]. Therefore, it is important to include the information of ocean eddies while conducting TC intensity forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…The observational and numerical studies have shown that rapid intensification can occur when the storm passes over a warm ocean eddy. In contrast, when the TC encounters a cold ocean eddy, the SST cooling can be enhanced, and thus TC intensity would be further limited due to the stronger negative feedback associated with the decrease of the heat flux from the ocean [ Lin et al ., , ; Wu et al ., ; Sung et al ., ; Walker et al ., ]. Therefore, it is important to include the information of ocean eddies while conducting TC intensity forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2014) illustrated the effects of super typhoons on the 40 strength, spatial area, and kinetic energy of COEs. Some observations 43 have found the long-lived biophysical response in COEs by remote sensing and Argo floats (Sun 44 et al 2010;Sun et al 2012;Walker et al 2014); however, the dynamic processes need to be 45 investigated further by numerical model. Some observations 43 have found the long-lived biophysical response in COEs by remote sensing and Argo floats (Sun 44 et al 2010;Sun et al 2012;Walker et al 2014); however, the dynamic processes need to be 45 investigated further by numerical model.…”
Section: Introduction 28mentioning
confidence: 99%
“…Thermal structures of the upper ocean in the vicinity of a TC path can influence the TC intensity. In particular, mesoscale warm core ocean eddies (WCE) provide relatively warmer ocean temperature compared to the surrounding water and can lessen the TC‐induced upper ocean cooling, while the cold core eddies (CCE) tend to produce large ocean cooling and reduce the upward surface enthalpy fluxes (e.g., Lin et al ., ; Walker et al ., ). On the other hand, ocean eddies may change the ocean mixed‐layer depth which is the most important factor in determining the magnitude of the feedback to TC (Wu et al ., ).…”
Section: Introductionmentioning
confidence: 97%